Pengaruh Visualisasi Iklan Sosial Media Dalam Sistem Pemasaran Barang Rumah Tangga Terhadap Keputusan Pembelian Pada Masyarakat Desa Karang Anyar Kecamatan Pegajahan Kabupaten Serdang Bedagai - Muhammad Iqbal Sayuti Harahap; Annio Indah Lestari Nasution; Muhammad Ikhsan Harahap (Universitas Hamzanwadi, 2023)
This study aims to determine the effect of visualization of social media advertisements on purchasing decisions for the people of Karang Anyar village. The method used is quantitative, with 100 samples and 2,220 populations. The data collection technique was by distributing questionnaires and processed with the help of the SPSS 23 application. This study used simple linear regression analysis to examine the results of the questionnaire data so that the results obtained were that there was an influence between the visualization of social media advertising and purchasing decisions. This states that people pay attention to visualizing advertisements on social media, in this case, encouraging people's decisions to buy a product